A new approach to the fundamental limits in the theory of limits - Mironenko, L.P. (Искусственный интеллект, 2014)
The purpose of the paper is an alternative way of obtaining of the fundamental limits in the elementary theory of limits. The approach uses two double inequalities. The method is applied to the both limits simultaneously, that makes the theory universal. Proof of the limits is quite new and original. Apart from that our theory gives many new representations of the limits (total 37).